2016
DOI: 10.1136/bjsports-2015-095308
|View full text |Cite
|
Sign up to set email alerts
|

No economic benefit of early knee reconstruction over optional delayed reconstruction for ACL tears: registry enriched randomised controlled trial data

Abstract: ISRCTN84752559.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Nwachukwu et al [ 32 ] evaluated the cost-effectiveness analyses in orthopaedic sports medicine literature and suggested that ACL reconstruction was cost-effective. On the other hand, a recent study published by Kiadiliri et al [ 26 ] found no statistically significant difference in economic value in terms of early ACL reconstruction compared with rehabilitation and ACL reconstruction when needed. They may improve the outcome, but at greater expense and with higher administrative costs, plus lapses in quality [ 2 ].…”
Section: Discussionmentioning
confidence: 95%
“…Nwachukwu et al [ 32 ] evaluated the cost-effectiveness analyses in orthopaedic sports medicine literature and suggested that ACL reconstruction was cost-effective. On the other hand, a recent study published by Kiadiliri et al [ 26 ] found no statistically significant difference in economic value in terms of early ACL reconstruction compared with rehabilitation and ACL reconstruction when needed. They may improve the outcome, but at greater expense and with higher administrative costs, plus lapses in quality [ 2 ].…”
Section: Discussionmentioning
confidence: 95%
“…There is a delicate balance between desirable and undesirable treatment consequences. Costs for ACLR outweighs costs for non-operative treatment, and an early ACLR is not more beneficial in terms of costs, compared to a delayed ACLR 61 . With regard to values and preferences, patients often prefer ACLR, which seems to be founded in beliefs that ACLR is a necessary treatment to allow physical activity 120 .…”
Section: Reasons For Choice Of Treatmentmentioning
confidence: 99%
“…Several studies have shown that not all PRP product systems yield similar biologic parameters, where the final PRP injectates vary greatly and have differing effects on tendon cells. [5][6][7] Specifically, Yan et al 8 showed that leukocyte-poor PRP (Lp-PRP) improved Achilles tendon healing and was a preferable option for Achilles tendinopathy compared with leukocyterich PRP (Lr-PRP). Interestingly, in the 3 included randomized controlled trials that reported no benefits of PRP, [9][10][11] an Lr-PRP system (GPS, Zimmer-Biomet, Warsaw, IN; Genesis CS, VetStem, Biopharma, Poway, CA) was used, which is already known to be less effective than Lp-PRP in the treatment of Achilles tendinopathy.…”
mentioning
confidence: 99%
“…Interestingly, in the 3 included randomized controlled trials that reported no benefits of PRP, [9][10][11] an Lr-PRP system (GPS, Zimmer-Biomet, Warsaw, IN; Genesis CS, VetStem, Biopharma, Poway, CA) was used, which is already known to be less effective than Lp-PRP in the treatment of Achilles tendinopathy. 7,8 The single study that used the Lp-PRP system (ACP; Arthrex, Munich, Germany), included in this analysis, reported excellent outcomes in the treatment of Achilles tendinopathy. 12 This finding underscores the difference of effect between Lr-PRP and Lp-PRP in treating Achilles tendinopathy.…”
mentioning
confidence: 99%
See 1 more Smart Citation